Degrowth or barbarism? An exploration of four circular futures for 2050 - Calisto Friant, Martin; Vermeulen, Walter J. V.; Salomone, Roberta (Frontiers in Sustainability, 2025)
There are many competing visions regarding what a circular economy transition entails and how it would transform our social, economic, environmental, technological, and political systems. This paper sheds light on these different circular discourses by asking the following research questions: what future would different circularity discourses envision for 2050? To answer this question, this paper uses scenario planning methods to explore how four circular discourses developed in a 2x2 typology of circularity thinking would imagine the future. Results examine how these four discourses would organise and operationalise circular transport, energy, agriculture, and industrial systems in 2050. Results also explore the political systems and governance processes they would establish and the type of society, culture, worldview and lifestyles they would create. Moreover, the paper analyses each scenario’s desirability (in terms of their potential to foster socio-ecological well-being) and ecological plausibility, as well as the level of societal change potentially needed to bring them about. The paper concludes that there is a real danger in following growth-based circular discourses and scenarios because their visions cannot be implemented within the biophysical boundaries of the Earth. Indeed, over 50 years of academic research have demonstrated that decoupling economic growth from environmental degradation fast enough to prevent climate breakdown and biodiversity collapse is impossible. On the other hand, degrowth-oriented approaches to circularity might shed light on circular futures that can allow all present and future generations to live a good life within the ecological boundaries of the Earth. This research recommends fostering democratic transformations such as citizen assemblies, participatory budgeting and worker-owned non-profit cooperatives as potential avenues to more inclusive, sustainable and socially just futures. This paper is thereby valuable to researchers, citizens and practitioners who seek to better understand the socio-ecological implications of different circular futures and envision desirable and viable alternatives.